1998
DOI: 10.1002/(sici)1097-0231(19981030)12:20<1485::aid-rcm333>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Application of high performance liquid chromatography/tandem mass spectrometry in the environmental and biological monitoring of health care personnel occupationally exposed to cyclophosphamide and ifosfamide

Abstract: Twenty four workers (10 involved in the preparation and 14 in administration) exposed to cyclophosphamide (CP) and ifosfamide (IF) in two Italian hospitals were monitored. The extent of exposure was assessed by the analysis of air samples, wipe samples, pads and gloves. Urinary excretion at the beginning and at the end of the work shift was also measured by liquid-liquid extraction and analysis by high performance liquid chromatography/tandem mass spectrometry. Three out of 24 air samples were positive for CP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
57
0
2

Year Published

1999
1999
2014
2014

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(65 citation statements)
references
References 10 publications
(11 reference statements)
5
57
0
2
Order By: Relevance
“…The same kind of results were observed in a study developed in Italian hospitals (Castiglia et al 2008) that concluded that the cause of contamination of this type of surfaces (phones, chairs, closets, and others not directly related with drug preparation) were the workers gloves that were not removed immediately after drug handling. As in our study, other studies (Minoia et al 1998;Mason et al 2005;Fransman et al 2004Fransman et al , 2007 found contamination on the worker's gloves. For instance, the gloves that was possible to sample in the administration unit of hospital B, showed contamination by 5FU (11.4 ng/cm 2 ) and, also, high amounts of PTX (414.7 ng/cm 2 ).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The same kind of results were observed in a study developed in Italian hospitals (Castiglia et al 2008) that concluded that the cause of contamination of this type of surfaces (phones, chairs, closets, and others not directly related with drug preparation) were the workers gloves that were not removed immediately after drug handling. As in our study, other studies (Minoia et al 1998;Mason et al 2005;Fransman et al 2004Fransman et al , 2007 found contamination on the worker's gloves. For instance, the gloves that was possible to sample in the administration unit of hospital B, showed contamination by 5FU (11.4 ng/cm 2 ) and, also, high amounts of PTX (414.7 ng/cm 2 ).…”
Section: Discussionsupporting
confidence: 85%
“…Presently, due to the evolution of the technical protection resources available in the workplaces, such as biological safety cabinets (BSC) and hoods, the most common route of exposure is skin absorption rather than inhalation or ingestion (Minoia et al 1998). Recent studies showed also that antineoplastic levels in air samples were not significantly detected, suggesting that inhalation might have a lower impact when assessing exposure (Mason et al 2005;Connor et al 2010;Huang et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…10,11,13,[17][18][19] These methods have been used to study air concentrations of CP at different workplaces. In previous studies different types of filters have been used to collect particles of CP.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, in studies of external exposures [Sessink et al,1992;Minoia et al,1998;Sabatini et al,2005;Hedmer et al,2008] and studies in internal exposures [Hirst et al,1984;Sessink et al,1992Sessink et al, , 1994Sessink et al, , 1995Ensslin et al,1994;Burgaz et al,1999;Pethran et al,2003], cyclophosphamide was frequently used as a marker of occupational exposures because of its slight volatility and human genotoxicity [Connor et al,2000], reproductive toxicity [Anderson et al,1995], carcinogenicity [IARC,1981], and ease of detection [Turci et al,2002;Barbieri et al,2006].…”
Section: Discussionmentioning
confidence: 99%